The Transformation Of Islamic Religious Education In The Face Of Religious Moderation In The Digital Era - Muhammad Alfi Syahrin; Widodo Widodo; Florika Afriana; Hilda Amidayati (JURNAL PEDAGOGY, 2025)
The transformation of Islamic religious education is an urgent need in the digital era marked by the rapid flow of information and social change. The presence of digital technology opens up new opportunities for the learning process, but it also brings challenges, especially in maintaining moderate Islamic values. Islamic religious education is no longer only oriented to the transfer of knowledge, but must also be able to form the character of students who are tolerant, inclusive, and adaptive to diversity, in line with the principles of religious moderation. However, many previous studies have focused on aspects of the curriculum or conventional methods without highlighting in depth how to integrate the values of moderation in Islamic education practices in the digital realm. There is a gap between the theory of religious moderation and its application in the digital-based education system, especially in the context of Islamic education in Indonesia. Therefore, the formulation of the problem in this study is: how to transform Islamic religious education in facing the challenges of religious moderation in the current digital era. This research uses a qualitative approach with literature study methods and case studies on several Islamic educational institutions that have implemented moderation-based learning digitization programs. The results of this study are expected to make a practical contribution to the development of Islamic education models that are relevant to the digital era and theoretically enrich the literature on the integration of moderation values in religious education. These findings are also the basis for policy recommendations for educational institutions and related policymakers.